2014
DOI: 10.1161/circresaha.113.301720
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Mononuclear Phagocyte Network Underlies Chronic Inflammation and Disease Progression in Heart Failure

Abstract: Rationale The role of mononuclear phagocytes in chronic heart failure (HF) is unknown. Objective Our aim was to delineate monocyte, macrophage, and dendritic cell trafficking in HF and define the contribution of the spleen to cardiac remodeling. Methods and Results We evaluated C57Bl/6 mice with chronic HF 8 weeks after coronary ligation. As compared with sham-operated controls, HF mice exhibited: (1) increased proinflammatory CD11b+F4/80+CD206− macrophages and CD11b+F4/80+Gr-1hi monocytes in the heart and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
321
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(349 citation statements)
references
References 49 publications
12
321
1
2
Order By: Relevance
“…Because the immune system plays an important role not only in infarct healing but also in adverse remodeling and progression of heart failure,20, 21 we evaluated the myocardial content of immune cells with CD45 staining (Figure 5A). The number of CD45 POS cells in the risk and noninfarcted regions was quantitated and expressed as a percent of total cells counted in the corresponding region (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Because the immune system plays an important role not only in infarct healing but also in adverse remodeling and progression of heart failure,20, 21 we evaluated the myocardial content of immune cells with CD45 staining (Figure 5A). The number of CD45 POS cells in the risk and noninfarcted regions was quantitated and expressed as a percent of total cells counted in the corresponding region (Figure 5B).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the involvement of monocytes/macrophages in the development and progression of ischemic cardiomyopathy was described (3,50). It was reported that macrophages gradually expand within the remote myocardium during the course of heart failure, while macrophage numbers within the scar wane ( Figure 1C) (3).…”
Section: Macrophages In Post-mi Heart Failurementioning
confidence: 94%
“…Finally, since apo A-I induces regulatory T cells (Wilhelm et al 2010), which protect against the pro-inflammatory status of endothelial cells , an induction in regulatory T cells following apo A-I transfer may also partly account for the reduced cardiac inflammation in diabetic rats. Since inflammation triggers fibrosis (Ismahil et al 2013;Savvatis et al 2012;Westermann et al 2011), the less pronounced diabetes-induced cardiac fibrosis (cfr. infra) following apo A-I transfer might partly be explained by the decrease in cardiac inflammation.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-induced Cardiacmentioning
confidence: 99%